Subalternity in the Cebuano poems of Michael Obenieta (A postcolonial approach to the study of the selected Cebuano poems of Michael Obenieta). - Buac, Abigail C.
This study examines eleven Cebuano poems of Michael "Myke" Obenieta and reviews cultural-historical studies related to the concept of subalternity as an aspect of postcolonialism. The prevalent literary element in Myke's poems is imagery. Other literary elements present are similes, metaphors, personifications, and hyperboles which contribute to the effectiveness of imagery. The style of writing employed by the author is adopted from the Western way of writing - the free verse - although he uses the formal Cebuano language in presenting images of Cebuanos and the aspects of their everyday life. These eleven Cebuano poems contain symbols and images of subjugation, absorption, domination, and subordination which characterizes the Cebuanos as subalterns. Myke, as he explores the Cebuano culture and reflect them in these eleven poems, contribute to the development of the Cebuano literature ; a new trend in the study of Cebuano literary culture.